Adjuvant Trastuzumab Therapy: Can We Balance Efficacy and Safety?. (17th July 2019) - Barron, Carly C.; Tyagi, Nidhi Kumar; Alhussein, Muhammad Mustafa; Mukherjee, Som D.; Ellis, Peter M.; Dhesy‐Thind, Sukhbinder; Leong, Darryl P.
Abstract: Trastuzumab is an effective treatment for HER2‐positive breast cancer. Current guidelines recommend withholding trastuzumab in patients experiencing a significant asymptomatic decline in left ventricular function. In this commentary, we discuss the survival benefits afforded by trastuzumab juxtaposed against the risk of trastuzumab‐mediated cardiotoxicity. It is not known whether the net benefit of continuing trastuzumab in the setting of mild cardiotoxicity outweighs the associated risks. We describe a potential approach undertaken by our group, and others, and call for a randomized trial. Abstract : Trastuzumab is a highly effective treatment for HER2‐positive breast cancer, and discontinuation can lead to adverse cancer outcomes for patients. This commentary considers these facts in light of existing guidelines recommending withholding trastuzumab in patients at risk for cardiotoxicity.